Traditional Chinese medicine as a promising choice for future control of PEDV - Conghao Ji; Shuxuan Li; Cunhai Hu; Tongtong Liu; Qingqing Huang; Mengyuan Yang; Mengxin Yang; Qianqian Wang; Aifang Li; Dandan Guo; Yu Huang; Sugai Yin; et al. (Virus Research)
Porcine epidemic diarrhea virus (PEDV) is the major agent of the recent outbreaks of diarrhea in piglets, which has caused huge economic losses to the global swine industry. Since traditional vaccine strategies cannot provide complete protection for piglets, the development of safe, effective, and economical antiviral drugs is urgently needed. For many years, traditional Chinese medicines (TCMs) have been broadly applied for viral infectious diseases, exhibiting advantages such as abundant resources, lower toxicity, and minimal drug resistance. Many Chinese herbal monomers, single herbal extracts derived from these traditional drugs, and Chinese herbal recipes exhibit significant anti-PEDV effects in vitro and/or in vivo by targeting multiple sites and perspectives, including inhibition of the viral life cycle, anti-inflammation effects, enhancement of the host immune response, modulation of reactive oxygen species, and apoptosis. However, to date, no review has been published on the anti-PEDV effects of TCM. Therefore, this review summarizes the current control strategies for PEDV and systematically analyses the research progress of TCMs against PEDV. Furthermore, the future directions including the integration of nanotechnology and artificial intelligence with TCMs are also discussed. This review will provide a valuable reference for future studies on TCMs in antiviral research.